Jovens negros, futebol, educação e relações raciais : o projeto esportivo Digoreste - Britto, Walfredo (2006)
This study it investigated aspects of the escolarização; of the relation with the soccer and the perception of the racial relation of young blacks who frequented PROJECT DIGORESTE In the SPORTS of the Direction of Sport and Leisure - DIDEL of the Municipal City hall of Cuiabá - TM, for the practical one of the soccer, in 2005. Of qualitative nature, for its recital the research was anchored in the contribution of Daolio, Mario Son, Lever and Vieira for the question of the soccer and racial relations s we appeal the Brave, Oliveira, D ' Adesky and Petruccelli. For the field work we select pupils of the project through the question color for questionnaire application. The analysis of the collected empirical material showed that PROGRAM DIGORESTE, although to contribute with the rise of auto-esteem of the young blacks, waving to them with the perspective to project a future of ascension through the soccer and infusing the interest to them for the continuity in the studies, is not possible to perceive a contribution of the Project for the advance of the awareness of these young on its negritude.